Can integrated care interventions strengthen primary care and improve outcomes for patients with chronic diseases? A systematic review and meta-analysis - Yuqi Zhang; Jonathan Stokes; Laura Anselmi; Peter Bower; Jin Xu (Health Research Policy and Systems)
Abstract Background An increasing number of people live with chronic disease or multi-morbidity. Current consensus is that their care requires an integrated model bringing different professionals together to provide person-centred care. Although primary care has a central role in managing chronic disease, and integration may be important in strengthening this role, previous research has shown insufficient attention to the relationships between primary care and integration. This review summarizes primary care involvement in integrated care interventions and assesses the effect of those interventions on a range of measures of primary care functions and wider outcomes. Methods We searched Medline and Embase using terms for “integrated care”, “chronic disease” and “multimorbidity”. We included integrated care interventions involving different levels of care organizations or different care sectors. Risk of bias was appraised, and the contents of integrated care interventions assessed using the Sustainable intEgrated care modeLs for multi-morbidity: delivery, FInancing and performancE (SELFIE) conceptual framework. Effectiveness of integrated care interventions was assessed using meta-analysis of primary care functions (access, continuity, comprehensiveness and coordination) and wider outcomes (patient health and mortality, hospital admissions and costs). Sub-group analyses were conducted for different types of primary care involvement. Results From 17,752 studies screened, 119 studies on integrated care were identified, of which 69 interventions (58%) involved primary care. Meta-analyses showed significant beneficial effects on two measures of primary care function: access (effect size: 0.17, 95% CI 0.05–0.29) and continuity (effect size: 0.32, 95% CI 0.14–0.50). For wider outcomes, the only statistically significant effect was found on costs (effect size: 0.02, 95% CI 0.02–0.03). Conclusions Integrated care interventions involving primary care can have positive effects on strengthening primary care functions, but these benefits do not necessarily translate consistently to wider outcomes.